The Relevance of Kafa'ah in Islamic Law to Mandar Custom: A Case Study in Polewali Mandar Regency - Muhammad Haikal (al-Afkar, Journal For Islamic Studies, 2026)
This study examines the relevance of the concept of kafa’ah in Islamic law and Mandar customs through a case study in Polewali Mandar Regency. The purpose of this study is to determine the concept of kafa’ah in Mandar customs according to traditional leaders and cultural experts, the Islamic legal perspective on kafa’ah, and the relevance of both. The method used is qualitative with a comparative analysis approach, based on data from interviews with traditional leaders and Mandar cultural experts and studies of classical and contemporary fiqh books. The results show that in Islamic law, kafa’ah is an important principle of marriage to maintain household harmony. Aspects considered include compatibility of religion, lineage, wealth, occupation, physical condition, and Islamic faith, with the main emphasis on compatibility of religion or morals. In Mandar customs, kafa’ah places greater emphasis on descent or social strata, which are divided into several groups, such as royal nobility (todiang laiyana), customary nobility (tau pia), free people (tau samar), and slaves (batua), while also considering religion, economics, blood relations, and health, particularly hereditary diseases such as leprosy (karae uli’) and poppoang. The similarity between the two lies in respect for religion, while the difference lies in the Mandar custom’s emphasis on lineage, which is less in line with the principle of Islamic equality. Over time, some traditional leaders consider the emphasis on lineage to be no longer relevant, although some still maintain it.